2017
DOI: 10.1097/jom.0000000000001061
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Hardmetal Production Workers

Abstract: This study does not provide evidence for elevated lung cancer risks. Methodologic limitations, incomplete ascertainment of death causes in particular, impede conclusions about exposure effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The authors also evaluated RRs across levels of cumulative exposure with adjustment for occupational co-exposures, reporting no increase in lung cancer risk for the group of workers with the highest cumulative exposure (RR ¼ 0.78, 95% CI: 0.26-2.4). Morfeld et al (2017) reported an SMR of 0.93 (95% CI: 0.68-1.25) for German workers compared to the national population and a hazard ratio (HR) of 1.09 (95% CI: 0.01-18.81) for a 1-unit increment in cumulative nickel exposure, with adjustment for occupational co-exposures. McElvenny et al (2017) reported an SMR of 0.91 (95% CI: 0.15-1.92) for workers in the UK with at least 20 years of employment, with no adjustment for important potential confounders.…”
Section: Evaluation Of Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors also evaluated RRs across levels of cumulative exposure with adjustment for occupational co-exposures, reporting no increase in lung cancer risk for the group of workers with the highest cumulative exposure (RR ¼ 0.78, 95% CI: 0.26-2.4). Morfeld et al (2017) reported an SMR of 0.93 (95% CI: 0.68-1.25) for German workers compared to the national population and a hazard ratio (HR) of 1.09 (95% CI: 0.01-18.81) for a 1-unit increment in cumulative nickel exposure, with adjustment for occupational co-exposures. McElvenny et al (2017) reported an SMR of 0.91 (95% CI: 0.15-1.92) for workers in the UK with at least 20 years of employment, with no adjustment for important potential confounders.…”
Section: Evaluation Of Study Resultsmentioning
confidence: 99%
“…Four cohorts were identified in the hardmetal production industry. These cohorts included multiple sites in the US (Marsh et al 2017a), UK (McElvenny et al 2017), Sweden (Svartengren et al 2017;Westberg et al 2017), and Germany (Morfeld et al 2017), where nickel was added as a trace element to hardmetal mixtures of tungsten carbide to impart specific properties and may also have been used as a binding agent, alone or in conjunction with cobalt. The ratio mean (i.e.…”
Section: Cohorts Of Workers Exposed To Metallic Nickelmentioning
confidence: 99%
See 2 more Smart Citations
“…No association has been found between increased respiratory cancer risk and inhalation exposure to metallic nickel outside the nickel refineries, when local populations were used as controls [57,58]. More recent cohort studies support the lack of association between exposure to metallic nickel and excess respiratory cancer [59][60][61][62][63].…”
Section: Inhalation Exposure Routementioning
confidence: 95%